AETIOLOGICAL FACTORS IN MECHANICAL INTESTINAL OBSTRUCTION - Asad, Shawana; Khan, Hafizullah; Khan, Ishtiaq Ali; Ali, Sher; Ghaffar, Salma; Rehman, Zia ur (Journal of Ayub Medical College Abbottabad, 2011)
Background: Intestinal obstruction occurs when the normal flow of intestinal contents is interrupted. The most frequent causes of intestinal obstruction are postoperative adhesions and hernias, which cause extrinsic compression of the intestine. Less frequently, tumours or strictures of the bowel can cause intrinsic blockage. Objective of the study was to find out the various aetiological factors of mechanical intestinal obstruction and to evaluate the morbidity and mortality in adult patients presenting to Surgical '˜A' unit of Ayub teaching hospital with mechanical intestinal obstruction. Methods: This cross-sectional study was conducted from March 2009 to September, 2009. All patients presenting with intestinal obstruction and were above the age of 12 years were included in the study. Patients with non-mechanical obstruction were excluded from the study and those who responded to conservative measures were also excluded. Results: A total of 36 patients with age ranging from 12 to 80 years (Mean age 37.72±19.74 years) and male to female ratio of 1.77:1, were treated for mechanical intestinal obstruction. The most common cause for mechanical intestinal obstruction was adhesions (36.1%). Intestinal tuberculosis was the second most common cause (19.4%), while hernias and sigmoid volvulus affected 13.9% patients each. Malignancies were found in 5.6% cases. Conclusion: Adhesions and Tuberculosis are the leading causes of mechanical intestinal obstruction in Pakistan. Although some patients can be treated conservatively, a substantial portion requires immediate surgical intervention. Keywords: Intestine, Mechanical (Dynamic), Intestinal obstruction.